Revolution in the Film US Directed by Jordan Peele - Anisah Qolby; Erniyanti Nur Fatahhela Dewi; Titi Dewi Rohati (Linguapedia, 2026)
This research analyzes the theme of revolution in Jordan Peele's film Us (2019). The film presents two opposing groups: people who live freely in the upper world and those who are trapped below in restricted and harsh conditions. This contrast becomes a metaphor for class struggle in capitalist societies. The writer uses Karl Marx’s theory of revolution and class struggle to examine how inequality and oppression can lead to rebellion. The study applies a qualitative descriptive method, focusing on content analysis of selected scenes, dialogues, and character actions. The findings show that the film portrays systemic inequality through mirrored behavior, spatial separation, and exploitation. Alienation is experienced collectively by the Tethered, who are stripped of voice, identity, and freedom. Their shared suffering and lack of agency eventually lead to class awareness and rebellion. Thus, Us reframes revolution as a rational and collective response to enduring structural violence. The study implies that popular films can serve as powerful cultural texts for understanding and critically examining social inequality, class conflict, and systemic oppression through a Marxist perspective. Future research is recommended to compare Us with other contemporary films that address class struggle or to apply different critical approaches, such as postcolonialism or intersectionality, to broaden the interpretation of social resistance in cinema.